Steady-State Growth and the Elasticity of Substitution - Andreas Irmen (University of Heidelberg, Department of Economics, 2010)
In a neoclassical economy with endogenous capital- and labor-augmenting technical change the steady-state growth rate of output per worker is shown to increase in the elasticity of substitution between capital and labor. This confirms the assessment of Klump and de La Grandville (2000) that the elasticity of substitution is a powerful engine of economic growth. However, unlike their findings my result applies to the steady-state growth rate. Moreover, it does not hinge on particular assumptions on how aggregate savings come about. It holds for any household sector allowing savings to grow at the same rate as aggregate output.
urn:nbn:de:bsz:16-opus-104381
Keywords: 330; Capital Accumulation; Elasticity of Substitution; Direction of Technical Change; Neoclassical Growth Model; Neoklassisches Wachstumsmodell; Wachstumstheorie; Faktorsubstitution; Substitutionselastizität; Investition; Technischer Fortschritt; Theorie